10. ASSESSMENT OF ANXIETY, DEPRESSION AND STRESS IN CANCER PATIENTS AT THONG NHAT HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Objectives: To assess the level and the relation of anxiety, depression and stress in cancer patient at Thong Nhat hospital.Subject and method: A cross-sectional study in cancer patients admitted to Oncology Department at Thong Nhat hospital from December 1, 2020 to May 31, 2021.Results: The proportion of cancer patients with depression, anxiety and stress was high. Nearly two-third (69.7%) of cancer patients had moderate or higher level of depression, more than half (56.8%) cancer patients had moderate or higher anxiety level and 50.30% cancer patienst were moderate and high level of stress. Most of cancer patients’ demographic factors were not associated with depression, anxiety and stress among cancer patients, but there are factors including cancer patients’ surgical status, type of cancer and pain level which were significantly associated with the depression score, anxiety score, and stress score of patients (p < 0.05). There were a statistically significant relationship between depression, anxiety, and stress with correlation coefficients of 0.848, 0.89 and 0.894, respectively.Conclusion: The result shows that levels of anxiety, depression and stress in cancer patients are relatively high. The main finding found that factors including surgical status, type of cancer, and pain level which associated with depression score, anxiety score and stress score of cancer patients, however, and more research is needed into the reasons for patients' anxiety, depression and stress. This study provides primary source for further interventional researches among cancer patients to improve the quality of life for patients in the near future.
Keywords: cancer; anxiety; depression; stress